2008
DOI: 10.1210/er.2008-0002
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in Men

Abstract: With the aging of the population, there is a growing recognition that osteoporosis and fractures in men are a significant public health problem, and both hip and vertebral fractures are associated with increased morbidity and mortality in men. Osteoporosis in men is a heterogeneous clinical entity: whereas most men experience bone loss with aging, some men develop osteoporosis at a relatively young age, often for unexplained reasons (idiopathic osteoporosis). Declining sex steroid levels and other hormonal cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
263
1
21

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 374 publications
(289 citation statements)
references
References 276 publications
(321 reference statements)
4
263
1
21
Order By: Relevance
“…(11)(12)(13) These two sets of observations are often presented as in conflict. (14) A recent review by Khosla and colleagues (15) concluded that the most appropriate definition for osteoporosis in men, in the absence of fractures, was a major unresolved issue and should be the focus of future research. This issue was specifically addressed in the population-based Canadian Multicentre Osteoporosis Study (CaMOS) cohort, one of the first population-based cohorts to include both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…(11)(12)(13) These two sets of observations are often presented as in conflict. (14) A recent review by Khosla and colleagues (15) concluded that the most appropriate definition for osteoporosis in men, in the absence of fractures, was a major unresolved issue and should be the focus of future research. This issue was specifically addressed in the population-based Canadian Multicentre Osteoporosis Study (CaMOS) cohort, one of the first population-based cohorts to include both men and women.…”
Section: Introductionmentioning
confidence: 99%
“…These properties, or bone 'qualities', are compromised with the emergence of age-related abnormalities in bone modelling and remodelling, the cellular machinery responsible for the attainment of peak bone strength during growth and its maintenance during adulthood. The abnormalities contributing to material and structural decay are: a negative bone balance produced by each basic multicellular unit (BMU), a sustained increase in remodelling intensity in midlife in women but not in men unless frankly hypogonadal, reduced periosteal apposition after completion of longitudinal growth and secondary hyperparathyroidism (Khosla et al 2006). However, the most important cause of bone loss is the increase in the intensity of bone remodelling on the trabecular, intracortical and endocortical bone surfaces (Amin & Felson 2001;Benito et al 2004).…”
Section: Qualities Of Bone In Menmentioning
confidence: 99%
“…Men with a deficiency of total testosterone were more likely to have rapid bone loss from the hip or to suffer from hip fractures following minimal trauma. Also men with osteoporosis were more likely to have a deficiency of testosterone and estradiol (Khosla et al 2006). …”
Section: Androgens and Bonementioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study about men and women who had suffered a hip fracture, the effectiveness of zoledronic acid was evaluated by means of the health-related quality of life, demonstrating a significant improvement of their functional scores [116] . Although there are not as many studies on the use of bisphosphonates in men as there are in women, some authors claim that their effectiveness is similar in both genders [117] . Finally, in prostate cancer patients treated with androgenic deprivation and presenting a strong BMD decrease, bisphosphonates have been proved as an effective therapy for bone loss [118,119] .…”
mentioning
confidence: 99%